Optimal rent extraction in pre-industrial England and France : default risk and monitoring costs - Mikael Priks (Center for Economic Studies and ifo Institute (CESifo), 2005)
Beginning in the mid-seventeenth century, England changed its system of raising revenues from tax farming, combined with the granting of monopolies, to direct collection within the government administration. Rents were then transferred from tax farmers and monopolists to the central government such that English public finances improved dramatically compared to both the old system and to its major competitor, France. We offer a theory explaining this development. In our view, a cost of tax farming is the ex-ante inefficiency due to the auction mechanism while a cost of direct collection is the ex-post monitoring cost the government incurs to prevent theft. When the monitoring cost is high the government therefore allows tax farmers to extract large rents to enhance their up-front payments. In addition, because revenues materialize late under direct collection, and since the government faces limited borrowing, a high default risk makes a system of up-front collection attractive. The results of the model are consistent with historical facts from England and France.
Keywords: H11; N43; 330; Direkte Steuer; Rententheorie; Steuer; Steuerfahndung; Kosten; Staatsbankrott; Agency Theory; Theorie; Grossbritannien; Frankreich